Keterlibatan Publik dalam Pembentukan Undang-Undang: Tinjauan Normatif terhadap Proses Legislasi Undang-Undang TNI - Wildan Budi Ardianto; Zacky Rayhan Ramadhan (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
This research aims to normatively analyze the role and implementation of public participation in the legislative process, specifically concerning the formation of the Indonesian National Armed Forces (TNI) Law. Public participation is an essential principle in a democratic state, ensuring the legitimacy, transparency, and accountability of legal products. This normative review focuses on the legal framework governing community participation in law making, as mandated by the 1945 Constitution of the Republic of Indonesia and related regulations. The analysis reveals a gap between the ideal normative principle of meaningful participation and the empirical practice in the legislation of the TNI Law. Legislative processes involving the defense and security sector are often overshadowed by issues of secrecy and limited information accessibility, thereby impeding substantial public participation. It is necessary to strengthen the regulatory framework and establish more open, inclusive, and continuous mechanisms to ensure that public aspirations and interests, including those of civil society groups and academics, are adequately considered at every stage of law formation, especially for strategic legislation like the TNI Law.